A new species of Isohypsibiid (Eutardigrada) from Sicily - Pilato, Giovanni; D’urso, Vera; Sabella, Giorgio; Lisi, Oscar (Zootaxa, 2019)
Dastych (2016) analysed the holotype of Isohypsibius tetradactyloides (Richters, 1907) and noticed that it possesses a very faint cuticular sculpture. For this and other characters, Dastych considered the species to be a synonym of Isohypsibius asper (Murray, 1906). The authors re-examined specimens attributed to Isohypsibius tetradactyloides by Pilato (1971) from two Sicilian rivers, and noticed that they cannot be attributed to Isohypsibius asper but to a new species. This new species belongs to the I. asper group, and is described here as Isohypsibius occultus sp. nov.. As the very faint cuticular ornamentation can be difficult to observe, the authors compared the new species with species having smooth cuticle or ornamented cuticle. Species with cuticular gibbosities or annulations, or clearly different in other characters, i.e. those with only two macroplacoids, the presence of a septulum, and cuticular bars on the legs, were excluded from comparison.